Temperature-dependent morphology of chemical vapor grown molybdenum disulfide - Wang, Yantao (2017)
Monolayered molybdenum disulfide (MoS2) is a 2D direct band gap semiconductor with promising potential applications. In this work, we observed the temperature dependency of the morphologies of MoS2 monolayers from chemical vapor deposition. At a low growing temperature below 850 °C, MoS2 flakes tend to be trianglular in shape. At 850–950 °C, hexagonal MoS2 flakes can be observed. While at a temperature over 950 °C, MoS2 flakes can form rectangular shapes. Complementary characterizations have been made to these samples. We also proposed a mechanism for such temperature-dependent shape evolution based on thermodynamic simulation.